Cytotoxic and Genotoxic Effects of Fluconazole on African Green Monkey Kidney (Vero) Cell Line - Correa, Regianne Maciel dos Santos (Biomed Res Int, 2018)
Fluconazole is a broad-spectrum triazole antifungal that is well-established as the first-line treatment for Candida albicans infections. Despite its extensive use, reports on its genotoxic/mutagenic effects are controversial; therefore, further studies are needed to better clarify such effects. African green monkey kidney (Vero) cells were exposed in vitro to different concentrations of fluconazole and were then evaluated for different parameters, such as cytotoxicity (MTT/cell death by fluorescent dyes), genotoxicity/mutagenicity (comet assay/micronucleus test), and induction of oxidative stress (DCFH-DA assay). Fluconazole was used at concentrations of 81.6, 163.2, 326.5, 653, 1306, and 2612.1μM for the MTT assay and 81.6, 326.5, and 1306μM for the remaining assays. MTT results showed that cell viability reduced upon exposure to fluconazole concentration of 1306μM (85.93%), being statistically significant (P<0.05) at fluconazole concentration of 2612.1μM (35.25%), as compared with the control (100%). Fluconazole also induced necrosis (P<0.05) in Vero cell line when cells were exposed to all concentrations (81.6, 326.5, and 1306μM) for both tested harvest times (24 and 48 h) as compared with the negative control. Regarding genotoxicity/mutagenicity, results showed fluconazole to increase significantly (P<0.05) DNA damage index, as assessed by comet assay, at 1306μM versus the negative control (DI=1.17 vs DI=0.28, respectively). Micronucleus frequency also increased until reaching statistical significance (P<0.05) at 1306μM fluconazole (with 42MN/1000 binucleated cells) as compared to the negative control (13MN/1000 binucleated cells). Finally, significant formation of reactive oxygen species (P<0.05) was observed at 1306μM fluconazole vs the negative control (OD=40.9 vs OD=32.3, respectively). Our experiments showed that fluconazole is cytotoxic and genotoxic in the assessed conditions. It is likely that such effects may be due to the oxidative properties of fluconazole and/or the presence of FMO (flavin-containing monooxygenase) in Vero cells.